Genetic polymorphism of bone morphogenetic protein receptor type-1 gene in Black Bengal goat and its association with litter size - KUMARI, RAJNI; DAYAL, SHANKER; KUMAR, SANJAY; LAL, S V; CHAKRABORTI, ASIT; BARARI, S K; DEY, AMITAVA (The Indian Journal of Animal Sciences, 2015)
The genetic polymorphism of the bone morphogenetic protein receptor type-1 gene (BMPR1B) was studied in 100 does of Black Bengal goats. The study revealed 2 genetic variants, A (0.25) and G (0.75) and 2 genotypes, AG (0.5) and GG (0.5). Genotypic and allelic frequencies at BMPR1B locus revealed the abundance of mutant type (G) nucleotide in Black Bengal goats. All animals, were found to carry the mutant allele. A positive correlation was observed between the litter size and mutant type genotype. Heterozygous carrier and homozygous carrier does had litter size of 1.6 ± 0.26 and 2.07 ± 0.28 respectively. The results showed that BMPR1 B polymorphism may be targeted for upgrading low prolific breeds of Indian goat by introgression of this mutation in non prolific breeds by crossing.